Formation, Development and Sharing of Green Collections as an Important Factor of Eco-Sustainability - Abdullayeva, Adila (ADA University Library, 2024)
Our main goal in this poster is to form a Green Collection of the Library-Information Center of our university, including books, articles and other types of documents in the field of the environment, ecology, green economy, safe food, energy saving, environmental management and other areas, and provide open access to it and promote the concept of green information literacy among the libraries of the country.
Keywords: Green collections; Sustainable libraries; Environmental practices in librarianship; UNEC